Macroeconomic Expectations and Credit Card Spending - Galashin, Mikhail; Kanz, Martin; Perez-Truglia, Ricardo (Review of Financial Studies, 2026)
We examine how macroeconomic expectations affect consumer decisions, using an experiment with 2,872 credit card customers at a large commercial bank. In the experiment, participants are randomized into receiving expert forecasts of inflation and the nominal exchange rate. We find that forecasts shift inflation and exchange rate expectations, but do not change spending or self-reported consumption plans as predicted by standard models of intertemporal choice. Results from a supplementary survey experiment suggest that consumers are sophisticated enough to anticipate nominal rigidities and reduce spending on durables for precautionary reasons, counteracting the effects predicted by standard models of intertemporal optimization.